A new name for an old problem. Metabolic dysfunction-associated steatotic liver disease - review of literature - Adrian Kruszewski; Anna Dąbrowska; Paulina Przybysz; Maja Kucharska; Monika Szyszka; Natalia Paduszyńska; Karolina Błaszczak (Nicolaus Copernicus University in Toruń, 2024)
Introduction: Metabolic dysfunction-associated steatotic liver disease (MASLD) was previously known as non-alcoholic fatty liver disease (NAFLD). MASLD is one of the most important and leading causes of liver disease worldwide. This disease is a public health challenge in the 21st century. Aim of the study: This article aims to present the latest literature data on MASLD. The study is intended to show what consequences are associated with changing the name of the disease and this article is purposive to be a vademecum of knowledge for practicing physicians. Material and methods: Comprehensive literature searches were performed across the main electronic databases of PubMed and GoogleScholar using the keywords: "metabolic-dysfunction associated steatotic liver disease", "MASLD", "non-alcoholic fatty liver disease" and "NAFLD" Conclusions: Most patients do not report any symptoms. It is important to identify patients at increased risk of MASLD. A fundamental role in prevention and treatment is lifestyle changes. The pharmacological approach includes among others use of antidiabetic drugs and treatment of other associated states.